The compound score in elite road cycling - Leo, P.; Spragg, J.; Wakefield, J.; Swart, J. (Journal of Science and Cycling, 2022)
Elite road cycling is characterized by racing over varied terrain, ranging from flat races to extremely mountainous terrain. Researchers have frequently attempted to quantify the performance characteristics of cyclists to predict race success based on external and internal load metrics including power output, heart rate and speed. Recent research reported a strong relationship between the power profile and race performance. However, to date, there is still an ongoing debate whether absolute power output; a mass exponent, or relative power; power output normalized to body mass, is more advantageous. For this reason, the current study used both absolute and relative power output to calculate a compound score to investigate its predictive ability for race performance.